Ayurveda's Contemporary Preventative Approach to Skin and Hair CareA Review Study : Life Sciences-Ayurveda - Patel, Dr Maltee; Joshi, Dr Dnyanesh; Kumar Patel, Dr Manish (International Journal of Life Science and Pharma Research, 2023)
: Cosmetics are practical items that are widely used across the world to preserve and enhance the look of the face and other body parts, such as the lips, hands, fingers, eyes, and hair, among others. The personal care industry is currently more concentrated on herbal cosmetics as nowadays it is fast growing segment with a vast scope of various expansions in coming years. Herbal cosmetics are the preparations that represent cosmetics associated with active bio - ingredients, nutraceuticals, or pharmaceuticals. The use of bioactive phytochemicals from various botanicals has a dual function: they are used as cosmetics to care for the body and its parts, and the botanical components impact the skin's biological processes. Identifying the phytochemicals for skin and body care products is greatly aided by our historical understanding of the utilization of plant riches as documented in the Ayurveda, Siddha, Unani, and Tibetan systems of medicine. The development of Nobel cosmeceuticals for skin & body care illnesses will require the necessary efforts to associate current cosmetology with bioactive components based on our traditional system of medicine. Additionally, it significantly polluted the environment and disrupted our ecosystem. To enhance people's health and the quality of their lives and address the limitations of the allopathic system, both contemporary and conventional approaches must be used in addition to it. This has resulted in a rise in the use of herbal medications, cosmetics, neutraceuticals, and natural dyes. The aim of this review is to demonstrate the preventive methods of Ayurveda for skin and hair care in the contemporary period and to describe, based on a literature review, the relationship between Ayurveda and cosmetics. The knowledge of medicinal plants used by the people is well-known in its culture and tradition. The association between Ayurveda and cosmeceuticals has also been reviewed in this article.